Pengembangan Sistem Pemasaran Melalui Digital Marketing dan Mengimplementasikan Promotion Mix pada Perusahaan Jasa PT. Canindo Perkasa Mandiri Batam - Wisnu Yuwono; Yohanes Aprialdy Simanungkalit (ConCEPt - Conference on Community Engagement Project, 2021)
This community service program aims to help partners market their products and increase their sales turnover, which is located at Ruko Harapan Business Center Blok B No. 17 Jl. KH Ahmad Dahlan Kel. Tj. Riau, Kec. Sekupang Batam City. This community service activity was carried out for approximately six months from August 2020 to January 2021 with the design, implementation, and mentoring system methods created. The results of the implementation of the sales promotion strategy are digital advertising, creating websites, creating e-catalogs, and making reports on the development of partners' businesses. In general, a successful program can be successful by looking at the indicators of all partner sales that have increased, first during the Covid-19 pandemic.